Hubungan Pengetahuan dan Sikap terhadap Kejadian Preeklampsia Pada Ibu Hamil Di Wilayah Puskesmas Tangeban Kecamatan Masama Kabupaten Banggai - Nurnaningsih Yunus; Andi Nurlinda; Muh. Khidri Alwi (Journal of Muslim Community Health, 2021)
Background: The incidence of severe pre-eclampsia and eclampsia increases the risk of adverse events in labor which consists of maternal and perinatal outputs. The delivery outcome in eclampsia depends on the gestational age at disease onset, the quality of disease management, and the presence or absence of other medical illnesses. The purpose of this study was to analyze the association of knowledge and attitude with preeclampsia in pregnant women in the Tangeban Public Health Center, Masama District, Banggai Regency. Methods: This type of research is an analytic survey with a cross sectional research design. The sample in this research was all pregnant women, both preeclampsia and not in the Tangeban Puskesmas area, Masama sub-district, Probi regency, totaling 57 people. Results: There was no relationship between knowledge of the incidence of preeclampsia in pregnant women and there was a relationship between attitudes towards the incidence of preeclampsia in pregnant women in the Tangeban Public Health Center, Masama District, Banggai Regency. Conclusion: This study is expected to be used as an evaluation material for health centers related to factors related to preeclampsia in pregnant women in the Tangeban Community Health Center, Banggai Regency.